Numerical Analysis of the Seismic Response of Tunnel Composite Lining Structures across an Active Fault - Zude Ding; Mingrong Liao; Nanrun Xiao; Xiaoqin Li (Advances in Materials Science and Engineering)
The mechanical properties of high-toughness engineering cementitious composites (ECC) were tested, and a damage constitutive model of the materials was constructed. A new aseismic composite structure was then built on the basis of this model by combining aseismic joints, damping layers, traditional reinforced concrete linings, and ECC linings. A series of 3D dynamic-response numerical models considering the composite structure-surrounding rock-fault interaction were established to explore the seismic response characteristics and aseismic performance of the composite structures. The adaptability of the structures to the seismic intensity and direction was also discussed. Results showed that the ECC material displays excellent tensile and compressive toughness, with respective peak tensile and compressive strains of approximately 300- and 3-fold greater than those of ordinary concrete at the same strength grade. The seismic response law of the new composite lining structure was similar to that of the conventional composite structure. The lining in the fault zone and adjacent area showed obvious acceleration amplification responses, and the stress and displacement responses were fairly large. The lining in the fault zone was the weak part of the composite structures. Compared with the conventional aseismic composite structure, the new composite lining structure effectively reduced the acceleration amplification and displacement responses in the fault area. The damage degree of the new composite structure was notably reduced and the damage area was smaller compared with those of the conventional composite structure; these findings demonstrate that the former shows better aseismic effects than the latter. The intensity and direction of seismic waves influenced the damage of the composite structures to some extent, and the applicability of the new composite structure to lateral seismic waves is significantly better than that to axial waves. More importantly, under the action of different seismic intensities and directions, the damage degree and distribution area of the new composite structure were significantly smaller than those of the conventional composite lining structure.